Blended-flipped classroom learning for physics students with the topic of the photoelectric effect - Alvama Pattiserlihun; Stephanie Jessy James Setiadi (Jurnal Inovasi Pendidikan IPA, 2020)
Blended-Flipped Classroom Learning is a learning method that combines blended learning with flipped classroom learning. This study aims to: (1). Design and implement Blended-Flipped Classroom Learning with the topic of Photoelectric Effect for Physics and Physics Education students in Modern Physics course; (2). Determine how the effect of Blended-Flipped Classroom Learning on student learning outcomes for the topic of Photoelectric Effect; (3). Determine students’ responses toward Blended-Flipped Classroom Learning for the topic of Photoelectric Effect. This research was descriptive and conducted at the Physics and Physics Education Department, Universitas Kristen Satya Wacana in the Modern Physics course. From the results of the research conducted it can be concluded that student learning outcomes after Blended-Flipped Classroom Learning were in the “high” and “very high” category, where most students (85.7%) were in the very high category. This result indicates that learning using Blended-Flipped Classroom Learning helps students to achieve optimal learning outcomes. Student responses to Blended-Flipped Classroom Learning were in the “good” category. It also shows that students' positive responses to the learning process can influence the optimization of their learning outcomes. This kind of learning model requires the teacher who acts as a facilitator, dynamist, evaluator and also justifier.